Effect of gut hormones on bone metabolism and their possible mechanisms in the treatment of osteoporosis - Liu, Hongyu; Xiao, Huimin; Lin, Sufen; Zhou, Huan; Cheng, Yizhao; Xie, Baocheng; Xu, Daohua (Frontiers in Pharmacology, 2024)
Bone is a highly dynamic organ that changes with the daily circadian rhythm. During the day, bone resorption is suppressed due to eating, while it increases at night. This circadian rhythm of the skeleton is regulated by gut hormones. Until now, gut hormones that have been found to affect skeletal homeostasis include glucagon-like peptide-1 (GLP-1), glucagon-like peptide-2 (GLP-2), glucose-dependent insulinotropic polypeptide (GIP), and peptide YY (PYY), which exerts its effects by binding to its cognate receptors (GLP-1R, GLP-2R, GIPR, and Y1R). Several studies have shown that GLP-1, GLP-2, and GIP all inhibit bone resorption, while GIP also promotes bone formation. Notably, PYY has a strong bone resorption-promoting effect. In addition, gut microbiota (GM) plays an important role in maintaining bone homeostasis. This review outlines the roles of GLP-1, GLP-2, GIP, and PYY in bone metabolism and discusses the roles of gut hormones and the GM in regulating bone homeostasis and their potential mechanisms.